Giant choledochal cyst and infantile polycystic kidneys as prenatal sonographic features of Caroli syndrome. Issue 1 (4th October 2019) - Traisrisilp, Kuntharee; Tongprasert, Fuanglada; Wannasai, Komson; Tongsong, Theera
Abstract: Caroli syndrome is a developmental disorder caused by complete or partial arrest of ductal plate remodeling, leading to dilated bile ducts along with fibrosis surrounding the portal tracts. It is most commonly associated with autosomal recessive polycystic kidney (ARPKD). We report a unique case of Caroli syndrome, diagnosed prenatally at 24 weeks of gestation in a 29‐year‐old Thai woman. Ultrasound findings revealed the association of a fetal giant choledochal cyst with ARPKD. Autopsy findings showed ductal plate malformation, typical of Caroli syndrome, associated with giant choledocal cyst and ARPKD.